2017
DOI: 10.1080/09712119.2017.1302876
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and reliability of techniques to estimate live cattle body weight

Abstract: Five different techniques of estimating the live cattle body weight were evaluated with the objective to identify the most reliable technique for use in the field. Weighbridge was used as the reference for other techniques. The measurement techniques evaluated were Weighbridge, Weigh tape, Rondo tape, Schaeffer's formula, Agarwal's formula, and calculator method. The body weights of 89 Brown Swiss and 34 Jersey Cross cattle were estimated by each technique. Compared with Weighbridge, the body weight estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
0
28
0
2
Order By: Relevance
“…In beef cattle, common indicators of undernutrition are bodyweight or body condition score (BCS), although their use at slaughter level is limited since they vary in terms of animal age, sex and breed, mature size, stage of pregnancy or gut fill (Nicholson & Sayers, 1987;Morris, Kenyon, & Burnham, 2002;Coopman, De Smet, Laevens, Van Zeveren, & Duchateau, 2009;Tebug, et al, 2016;Wangchuk, Wangdi, & Mindu, 2017). Normally, at the slaughterhouse, weight loss is calculated in groups or batches, not individually.…”
Section: Morphometric Indicatorsmentioning
confidence: 99%
“…In beef cattle, common indicators of undernutrition are bodyweight or body condition score (BCS), although their use at slaughter level is limited since they vary in terms of animal age, sex and breed, mature size, stage of pregnancy or gut fill (Nicholson & Sayers, 1987;Morris, Kenyon, & Burnham, 2002;Coopman, De Smet, Laevens, Van Zeveren, & Duchateau, 2009;Tebug, et al, 2016;Wangchuk, Wangdi, & Mindu, 2017). Normally, at the slaughterhouse, weight loss is calculated in groups or batches, not individually.…”
Section: Morphometric Indicatorsmentioning
confidence: 99%
“…It was ensured that the same set of butchers were not used for two consecutive days. The live weight of the cattle was estimated just before slaughter using the body dimension method [7]. After slaughtering, the entire stomach and intestinal wastes, which were extracted manually by the butchers, were collected from each cattle and weighed using an electronic scale (XY200st, Zhejiang, China).…”
Section: Intestinal and Stomach Wastes Measurement And Characterizationmentioning
confidence: 99%
“…69 Additionally, weight estimates based on body measurements of cattle (e.g. Schaeffer's 70 formula (Sastry et al, 1983)) or use of weigh tapes (Heinrichs et al, 2007) have been shown 71 to deviate from true weights (Wangchuk et al, 2017). More accurate measures can be 72 obtained from scales such as weigh crushes or weigh floors.…”
Section: Introduction 39mentioning
confidence: 99%